Neuromyelitis Optica: Review and Utility of Testing Aquaporin‐4 Antibody in Typical Optic Neuritis. Issue 4 (July 2018) - Seay, Meagan; Rucker, Janet C.
Abstract : Abstract: : Neuromyelitis optica (NMO) is an autoimmune, inflammatory demyelinating disorder often leading to severe vision impairment and disability. The discovery of a diagnostic biomarker, the aquaporin‐4 antibody (AQP4‐IgG), transformed the clinical diagnosis and treatment of NMO and broadened the spectrum of disease [NMO spectrum disorders (NMOSD)]. Though the antibody is highly sensitive and specific to NMOSD, routine testing in patients with typical optic neuritis is considered controversial. This article will provide a brief review of NMOSD and highlight the pros and cons of routine testing in typical optic neuritis.